Monitoring Suhu Dan Infus Pasien Rumah Sakit Pasca Pandemic Berbasis Android - Denaldan Tabarui Landu Praing; Adelina Purba; syahri Muharom (Institut Teknologi Adhi Tama Surabaya, 2022)
Maintaining health is very vital for life, especially during the current COVID-19 pandemic era. One of the protocols imposed by the government for people doing their activities in public places is to check their body temperatures. Meanwhile, the periodic infusion checks of patients during the COVID-19 pandemic are still done manually by medical officers using complete PPE. When the infusion runs out, sometimes an officer comes late in changing the infusion, and this can be dangerous for a patient. To overcome the problems due to the unmonitored use of infusions and the patient's body temperature, a tool and a system are necessary. How the infusion works must be monitored so that its use can be better controlled. Therefore, the researcher raised the title of an Android-based monitoring system for patients’ temperature and infusion. To develop this system, the researcher employed contactless 906 as the temperature sensor and a load cell as the scale sensor to check the infusion. The load cell sensor would determine when the infusion weight varied, such as when the load cell was given an infusion load of 200 ml, the buzzer would sound like an alarm sensor. Data on body temperature and infusion weight would also be displayed on the LCD, which was then featured on the Android mobile phone application in the form of body temperature and infusion weight status in real time